The Effects of 8 weeks beta-hydroxy-beta-methylbutyrate (HMB) supplementation on body composition, inflammatory response and muscle damage after eccentric exercise in untrained males - Asjodi, Foad; Izadi, Azimeh (Progress in Nutrition, 2019)
Amino acids and their metabolite have shown anti-catabolic properties, through inhibition of muscle proteolysis and enhancement of protein synthesis. Beta-hydroxy-beta-methylbutyrate (HMB) is a derivative of the branched-chain amino acid leucine (LEU). In the context of exercise and recovery, several studies have reported the beneficial effects of HMB, but a limited number of studies have evaluated the efficacy of HMB intake among untrained subjects and also the duration of supplementation in previous studies is relatively short. In the present study, 40 untrained males were supplemented with HMB (3 g/ day) or placebo for 8 weeks and the effects of HMB on body composition and inflammation were investigated. The concentrations of creatine kinase (CK) and lactate dehydrogenase (LDH) were assessed at baseline, and at 1, 24, and 48 hours after exercise. The values of CK and LDH in HMB group were significantly lower (p=